Os phrasal verbs na produção escrita de aprendizes brasileiros de inglês como segunda língua: uma análise baseada em corpuss - Priscilla Tulipa da Costa (2017)
This research aims to investigate the use of phrasal verbs in academic essays written by Brazilian learners of English, in comparison with native speakers. The basis for the study is the importance of these grammatical structures to the proficiency in English, as well as the characteristics that make them difficult to be assimilated by non-native learners of the language. The work, which is descriptive, is based on Corpus Linguistics and was led by means of a methodology composed by quantitative and qualitative analysis of the phrasal verbs. As the learners corpus, we used the Br-ICLE. LOCNESS and BNC were used as control corpora. The data were processed and analyzed with the support of AntConc software. The results showed that phrasal verbs are, in general, less used in academic texts when compared to other types of multi-word verbs; however, it was also noted that some of the combinations produced have become typical of this kind of textual genre, what suggests that the use of phrasal verbs are increasing in formal texts. In addition, the study also showed that there are similarities and differences between the phrasal verb production in the groups analyzed. It was observed that the most used phrasal verbs by non-native are the same most used by native students; however, Brazilian students often use phrasal verbs differently from natives, suggesting a disagreement to the English language patterns. The research also indicates the need for further studies, especially in the field of semantics, for a better description of the phenomenon.